2011
DOI: 10.1364/oe.19.008641
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of light propagation in slotted resonator based systems via coupled-mode theory

Abstract: Abstract:Optical devices with a slot configuration offer the distinct feature of strong electric field confinement in a low refractive index region and are, therefore, of considerable interest in many applications. In this work we investigate light propagation in a waveguide-resonator system where the resonators consist of slotted ring cavities. Owing to the presence of curved material interfaces and the vastly different length scales associated with the sub-wavelength sized slots and the waveguide-resonator c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A ring resonator can be understood as the combination of a directional coupler and a feedback loop. First, the directional coupler is modeled by the input–output relations ( centertrue s 1 s 2 ) = ( centertrue t k k * t * ) ( lefttrue a 1 a 2 ) where k and t are the coupling and transmission coefficients, respectively. Both parameters are related by false| t false| 2 + false| k false| 2 = 1 for a lossless directional coupler.…”
Section: Resultsmentioning
confidence: 99%
“…A ring resonator can be understood as the combination of a directional coupler and a feedback loop. First, the directional coupler is modeled by the input–output relations ( centertrue s 1 s 2 ) = ( centertrue t k k * t * ) ( lefttrue a 1 a 2 ) where k and t are the coupling and transmission coefficients, respectively. Both parameters are related by false| t false| 2 + false| k false| 2 = 1 for a lossless directional coupler.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, microring resonators have been widely used in many fields due to their simple manufacturing process, excellent performance, flexible design, and small volume. In order to further enhance the interaction between optical fields and environmental mediums [1][2][3][4][5][6][7], nanoslot structures were introduced into the microring resonators, providing strong light confinements and localized field enhancements [8][9][10][11]. Recently, photonic crystal (PC) microring resonators have attracted great attentions for their ultracompact footprint, high Q-factor and small mode volume [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that narrow slot/slots in the waveguides further enhance the confinement of particular optical modes in the core region and reduce the bending loss of the waveguide [13]. Straight and bent waveguides with slotted cross-sectional regions can be combined to build microring resonators which have wide range of applications in integrated optics [14]. Slotted waveguides are particularly interesting in nonlinear optics due to their very small effective mode area and flat dispersion profiles [15,16].…”
Section: Introductionmentioning
confidence: 99%